Genotoxic Potential of the Metholic Extract of Psidium guineense Sw (Araçá verdadeiro) in Oral Mucosa Cells (Research, Society and Development, 2020)
The present research seeks to perform the analysis of the genotoxic potential of the methanolic extract of the plant Psidium (P.) guineense Sw, popularly known as ‘Araçá Verdadeiro’, against cells in the oral cavity. The donor's oral mucosa cells were exposed ex vivo to the methanolic extract of P. guineense in concentrations (50, 100, 500 and 1000 µg/mL) for 30 minutes, the cell pellet smear was made and subsequent fixation on slides stained with 2% Giemsa. The analysis was done using an optical microscope, the whole experiment carried out in triplicate. The data reveal that even at high concentrations (500 and 1000 µg/mL) of the methanolic extract of P. guineense Sw. Cell toxicity is considered low with a percentage of normal cells (94.5% to 94%) compatible with the negative control. Therefore, the methanolic extract, belonging to the species P. guineense Sw. has the bioactive potential that can be explored through the possible application of this compound as a phytotherapic, however more studies must be performed to better understand the toxicity profile of this product.